Addressing High Household Debt in Korea - Jones, Randall S.. (OECD Economics Department Working Papers, 2014)
Rising household debt has become a major policy concern in Korea. By the end of 2012, it had risen to 164% of disposable income, well above the OECD average of 133%. In addition to the economic impact and the risk to the financial sector, it raises social cohesion issues, as households with low income and credit ratings have limited access to financial markets and many are delinquent on their loans. It is essential to induce the soft-landing of household debt through a two-track approach: i) offering credit to households with low income and credit ratings and restructuring their debt, while limiting moral hazard and developing market-based lending; and ii) containing the risk caused by high household debt by strengthening prudential measures for financial institutions and improving mortgage lending by reducing the share of floating-rate and "bullet repayment" loans. This Working Paper relates to the 2014 OECD Economic Survey of Korea (www.oecd.org/eco/surveys/economic-survey-korea.htm)